1989
DOI: 10.1007/bf01071348
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of an ACE inhibitor, S-9780, in man: Evidence of tissue binding

Abstract: Pharmacokinetic data from 20-min constant rate infusions of the ACE inhibitor S-9780 1 mg to 16 subjects were studied for evidence of nonlinearity. A hierarchy of standard compartmental models and of nonlinear binding models was fitted to the data by least squares nonlinear regression and the most appropriate model was chosen on the basis of F-ratio tests, Schwarz criteria, and residual plots. A one-compartment model which included saturable tissue and plasma binding components allowed the best overall descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
2
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 14 publications
1
42
2
2
Order By: Relevance
“…Similar non linear relationships have been described where in vivo ACE inhibition is defined using angiotensin peptide ratios (Biollaz et al, 1982) although the exact description of the observed data is a matter of debate (Kelman et al, 1983). Preliminary studies using low dose intravenous infusions of ACE inhibitors have suggested that a sigmoid drug accumulation profile in venous plasma is evident which is best described by non linear saturable binding in which the pharmacokinetic model incorporates terms indicative of the proportions of drug bound to both plasma and tissue ACE (Lees et al, 1989). These studies have attempted to include statistical validation of the goodness of fit of the model but require further definition of the validity of the parameters generated.…”
Section: Kininase II Inhibitionmentioning
confidence: 83%
“…Similar non linear relationships have been described where in vivo ACE inhibition is defined using angiotensin peptide ratios (Biollaz et al, 1982) although the exact description of the observed data is a matter of debate (Kelman et al, 1983). Preliminary studies using low dose intravenous infusions of ACE inhibitors have suggested that a sigmoid drug accumulation profile in venous plasma is evident which is best described by non linear saturable binding in which the pharmacokinetic model incorporates terms indicative of the proportions of drug bound to both plasma and tissue ACE (Lees et al, 1989). These studies have attempted to include statistical validation of the goodness of fit of the model but require further definition of the validity of the parameters generated.…”
Section: Kininase II Inhibitionmentioning
confidence: 83%
“…In both groups of subjects, free plasma perindoprilat was eliminated in under 7 h, but there was a prolonged terminal elimination phase in excess of 40 h. This phenomenon is probably due to saturable binding to ACE [19,20]. Mathematical models have been published which better describe the pharmacokinetics of ACE-inhibitors after repeated administration and relate plasma concentration to ACE-inhibition [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic analysis The concentration-time profiles of perindoprilat using the different duration of infusions were characterised using a hierarchy of standard compartmental models and non-linear saturable binding models similar to those used in our previous work whose derivation and validation has been described (Lees et al, 1989). Briefly a range of multiexponential compartmental models (1 compartment (A), 2 compartment (B) and 3 compartment (C)) were fitted to the data using derivative-free, least squares, non-linear regression with the statistics package BMD-PAR on an ICL 3980 mainframe computer.…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have previously observed that the pharmacokinetic disposition of ACE inhibitors may be influenced by specific and saturable binding to plasma ACE (Francis et al, 1987) and/or tissue ACE (Lees et al, 1989). From limited observations we have suggested that pharmacokinetic models which include terms to describe this binding optimise the description of the pharmacokinetic data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation